A Deubiquitinating Enzyme Ubp14 Is Required for Development, Stress Response, Nutrient Utilization, and Pathogenesis of Magnaporthe oryzae - Wang, Zhao; Zhang, Hong; Liu, Caiyun; Xing, Junjie; Chen, Xiao-Lin (Frontiers in Microbiology, 2018)
Ubiquitination is an essential protein modification in eukaryotic cells, which is reversible. Deubiquitinating enzymes (DUBs) catalyze deubiquitination process to reverse ubiquitination, maintain ubiquitin homeostasis or promote protein degradation by recycling ubiquitins. In order to investigate effects of deubiquitination process in plant pathogenic fungus Magnaporthe oryzae, we generated deletion mutants of MoUBP14. Orthologue of MoUbp14 was reported to play general roles in ubiquitin-mediated protein degradation in S. cerevisae. The ΔMoubp14 mutant lost its pathogenicity and was severely reduced in mycelial growth, sporulation, carbon source utilization, and increased in sensitivity to distinct stresses. The mutant was blocked in penetration, which could due to defect in turgor generation. It is also blocked in invasive growth, which could due to reduction in stress tolerance and nutrient utilization. Deletion of UBP14 also led to accumulation of free polyubiquitin chains. Pulldown assay identified some proteins related to carbohydrate metabolism and stress response may putatively interact with MoUbp14, including two key rate-limiting enzymes of gluconeogenesis, MoFbp1 and MoPck1. These two proteins were degraded when the glucose was supplied to M. oryzae grown in low glucose media for a short period of time (~12 h), and this process required MoUbp14. In summary, pleiotropic phenotypes of the deletion mutants indicated that MoUbp14 is required for different developments and pathogenicity of M. oryzae.